Use of AHP Method in Cooperative Information System KJKS BMT Cangkeh Padang Village in the Provision of Medium and Lower Venture Capital Assistance - Ali Akbar Ritonga; Budianto Bangun; Iwan Purnama; Ibnu Rasyid Munthe; Windo (Jurnal Mantik, 2020)
Final entitled "Decision Support System Aid Medium-down venture capital in the Cooperative KJKS BMT Sub Cangkeh" created with the goal of Top That makes a Software Planned Hearts Able to help managers assess eligibility Decision A Customers obtain the loan. Software Singer is a venture capital decision-support framework. The authors use the Analytical Hierarchy Process (AHP) as a weighting tool to construct this scheme. The loan size, High turnover, and Dependants used three simple criteria. The decision support framework technology venture capital provision is the web-based programming language PHP and MySQL as database. The framework is structured to provide recommendations for customer eligibility with each requirement based on AHP calculation. With this framework, it is expected that managers can find the suitability of a customer's decision on a loan